MICRODATA STATISTICS FOR PUBLIC POLICY IN THE SOCIETY ERA 5.0 - Prasad, Arifiyanto (Public Policy Journal, 2022)
The era of society 5.0 brings a new concept so that people can enjoy technology in life comfortably. The problem faced today is about the gap in access to technology. The government needs to solve this problem by knowing the socio-economic conditions of the population as a whole. This research uses the type of library research. Based on the results of the 2021 Data Needs Survey, 92.52 percent of consumers use BPS data for development planning, monitoring, and evaluation. Seen by type, only 13.86 percent of BPS data consumers use micro data. In the context of government, micro-statistical data has been used to see development achievements. It is hoped that in the future, more public policies will be produced by various parties, supported by factual data and evidence.